Higher hemoglobin levels are an independent risk factor for adverse metabolism and higher mortality in a 20-year follow-up - Joona Tapio (Nature Portfolio, 2021)
Abstract The aim of this study was to cross-sectionally and longitudinally examine whether higher hemoglobin (Hb) levels within the normal variation associate with key components of metabolic syndrome and total and cardiovascular mortality. The study included 967 Finnish subjects (age 40–59 years) followed for ≥ 20 years. The focus was on Hb levels, cardiovascular diseases (CVDs) and mortality rates. Higher Hb levels associated positively with key anthropometric and metabolic parameters at baseline. At the follow-up similar associations were seen in men. The highest Hb quartile showed higher leptin levels and lower adiponectin levels at baseline and follow-up (p < 0.05) and lower plasma ghrelin levels at baseline (p < 0.05). Higher baseline Hb levels associated independently with prevalence of type 2 diabetes at follow-up (p < 0.01). The highest Hb quartile associated with higher serum alanine aminotransferase levels (p < 0.001) and independently with increased risk for liver fat accumulation (OR 1.63 [1.03; 2.57]) at baseline. The highest Hb quartile showed increased risk for total (HR = 1.48 [1.01; 2.16]) and CVD-related mortality (HR = 2.08 [1.01; 4.29]). Higher Hb levels associated with an adverse metabolic profile, increased prevalence of key components of metabolic syndrome and higher risk for CVD-related and total mortality.